2017
DOI: 10.17235/reed.2017.4545/2016
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in adults with irritable bowel syndrome in a Mexican specialist hospital. A cross-sectional study

Abstract: Background: Evidence shows the negative impact of irritable bowel syndrome on the quality of life of patients who suffer from the condition as compared to the general population.Objective: The objective of this study was to determine the health-related quality of life in adults with irritable bowel syndrome who are receiving treatment at a specialist hospital.Material and methods: The study had a cross-sectional prospective design. The study included consecutive patients diagnosed with irritable bowel syndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Symptoms of defecation disorders, such as diarrhea and constipation have been reported to decrease the QOL of patients with irritable bowel syndrome (IBS)[ 28 , 29 ]. Our results showed that symptoms of defecation disorders were factors that also had significantly adverse effects on living status and QOL in postgastrectomy patients.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of defecation disorders, such as diarrhea and constipation have been reported to decrease the QOL of patients with irritable bowel syndrome (IBS)[ 28 , 29 ]. Our results showed that symptoms of defecation disorders were factors that also had significantly adverse effects on living status and QOL in postgastrectomy patients.…”
Section: Discussionmentioning
confidence: 99%